Development of Curcumin-Loaded TiO2-Reinforced Chitosan Monofilaments for Biocompatible Surgical Sutures - Demirci, Fatma (Mdpi, 2025)
Sutures provide mechanical support for wound closure after various traumas and surgical operations. Absorbable sutures are increasingly favored as they eliminate the need for secondary procedures and minimize additional damage to the wound site. In this study, chitosan sutures were produced using the dry jet-wet spinning method, achieving number 7-0 sutures (approximately 76 mu m diameter) with a homogeneous surface. FTIR analysis demonstrated molecular interactions between chitosan and TiO2 or curcumin, confirming successful incorporation. The addition of 3% TiO2 increased the tensile strength of chitosan sutures by 12.32%, reaching 189.41 MPa. Morphological analysis revealed smooth surfaces free of pores and bubbles, confirming the production of high-quality sutures. Radical scavenging activity analysis showed that curcumin-loaded sutures exhibited 43% scavenging ability after 125 h, which was significantly higher compared to pure chitosan sutures. In vitro antibacterial tests demonstrated that curcumin-loaded sutures provided 98.87% bacterial inactivation against S. aureus within 24 h. Additionally, curcumin release analysis showed a cumulative release of 77% over 25 h. The bioactivity of the sutures was verified by hydroxyapatite layer formation after incubation in simulated body fluid, supporting their potential for tissue regeneration. These findings demonstrate that TiO2 reinforcement and curcumin loading significantly enhance the functional properties of chitosan sutures, making them strong candidates for biocompatible and absorbable surgical applications.
Keywords: dry jet-wet spinning; chitosan; suture; drug release; antioxidant activity; bioactivity